ANALYSIS OF THE EFFECT OF THE DOLLAR EXCHANGE RATE, INFLATION AND PRODUCTION ON TUNA PRODUCTION IN NORTH SUMATRA - Zuhri, Raihan; Rangkuty, Dewi Mahrani; Nasution, Lia Nazliana (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2024)
This study aims to determine the effect of the Dollar Exchange Rate, Inflation and Production on Tuna Fish Production in North Sumatra. The research method used in this research is associative method. This method aims to determine the relationship between two or more variables and the type of data used is quantitative. The data used is secondary data or time series from 2014 to 2023 sourced from the Statistics center and Bank Indonesia. The analysis method in this research is multiple linear regression method. The results of multiple linear regression show the results of this study that the dollar exchange rate has a negative and significant effect on tuna exports in North Sumatra. Inflation has a positive and significant effect on tuna exports in North Sumatra. Production has a negative and significant effect on tuna exports in North Sumatra. Based on the results of the F test the dollar exchange rate, inflation and production simultaneously have a significant effect on the export variable. The coefficient of determination test results show that there is a very close relationship between the dollar exchange rate, inflation and production on tuna fish exports in North Sumatra with a value (R-Square) of 0.905 or 90.5%. This result means that the magnitude of the influence of the dollar exchange rate, inflation and production on tuna fish exports in North Sumatra is 90.5% while the remaining 9.5% is influenced by factors not examined in this study.